2020
DOI: 10.1002/suco.201900359
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing the fire response of prestressed reactive powder concrete beams

Abstract: This paper presents the details of fire test on eight prestressed reactive powder concrete (RPC) beams cured with 150°C hot-air condition. The test specimens were varied in load ratios/degree, cover thicknesses of tendons, bonded and unbonded tendons, partial prestressing ratios. The thermal fields, deflections behaviour, effective prestress, fire endurance, failure modes, and crack patterns of the beams were observed and recorded during the tests. The post-fire tests observation reveals that no obvious therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Yang et al [17] demonstrated that decreasing load ratios and shear span to effective depth ratios increased fire resistance while increasing longitudinal reinforcement and stirrup ratios prevented cracking and reduced shear failure fragility. The research conducted by Yan's team [18][19][20] focused on the investigation of the response of pre-stressed ultra-high performance concrete (UHPC) beams subjected to ISO fire. They also developed a novel two-stage hot air curing method to mitigate spalling.…”
Section: Investigation Of the Post-fire Performance Of Beamsmentioning
confidence: 99%
“…Yang et al [17] demonstrated that decreasing load ratios and shear span to effective depth ratios increased fire resistance while increasing longitudinal reinforcement and stirrup ratios prevented cracking and reduced shear failure fragility. The research conducted by Yan's team [18][19][20] focused on the investigation of the response of pre-stressed ultra-high performance concrete (UHPC) beams subjected to ISO fire. They also developed a novel two-stage hot air curing method to mitigate spalling.…”
Section: Investigation Of the Post-fire Performance Of Beamsmentioning
confidence: 99%